Unpacking the effects of star architecture projects. (2nd February 2021) - Alaily-Mattar, Nadia; Bartmanski, Dominik; Dreher, Johannes; Koch, Michael; Löw, Martina; Pape, Timothy; Thierstein, Alain
Abstract : Purpose: To explain the process of how star architecture projects generate impact, one must first describe the outputs of such projects and then unpack the wide array of potential effects, which are generated by these outputs. This requires the application of multi-disciplinary research perspectives. Only then can one begin to systematically analyse the long-term impacts. The purpose of this paper is to illustrate how the complexity of such multi-disciplinary research exercise can be managed through the application of a methodological strategy aided by a conceptual impact model. Design/methodology/approach: A conceptual impact model is presented, which describes the process of the development of star architecture projects, the various outputs of these projects and the possible effects generated by these outputs. The effects of three case study star architecture projects are discussed. Findings: Empirical research findings indicate that while the isolation of effects serves the operationalisation of research, the investigation of the impact of star architecture projects on their respective cities must draw on the intertwinement of the fields of urban economy, society and morphology. The paper concludes by arguing for the application of the described methodological strategy as the basis for understanding in which dimensions a star architecture project generates impacts. Practical implications: The potential of the proposed impact model for urban analysis when considered as a field of intertwined relations is demonstrated in this article. It helps to reveal how particular local developments change the city significantly in socio-cultural and spatial terms. Originality/value: The transformative impact of star architecture projects and the role of economic and other effects in this process has hardly been studied, particularly in small and medium-sized cities. This article presents a unique multi-disciplinary research project approached consecutively in the aforementioned fields.